The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/bab.1419
|View full text |Cite
|
Sign up to set email alerts
|

A β‐mannanase from Paenibacillus sp.: Optimization of production and its possible prebiotic potential

Abstract: A thermotolerant bacterium Paenibacillus thiaminolyticus with an ability to produce extracellular β-mannanase was isolated from a soil sample. Bacterium produced 45 U/mL β-mannanase at 50 °C. The culture conditions for high-level production of β-mannanase were optimized. Optimized MS medium [wheat bran 2% (w/v), ammonium sulfate 0.3% (w/v), yeast extract, and peptone (0.025% each) pH 6.5] was inoculated with 2% of 16 H old culture.  The culture was incubated at 50 °C for 48 H resulting in 24-folds higher β-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…MOS are able to interfere in bacterial attachment (of Salmonella and E. coli ). In the intestinal tract, however, these oligosaccharides selectively promote the growth of beneficial bacteria, especially Lactobacillus and Bifidobacterium (Chauhan et al 2014 ; Dhawan et al 2015 ). Thus, the production of oligosaccharides with DP 3–4 makes A. terreus β-mannanase a good candidate for potential application in the feed industry.…”
Section: Discussionmentioning
confidence: 99%
“…MOS are able to interfere in bacterial attachment (of Salmonella and E. coli ). In the intestinal tract, however, these oligosaccharides selectively promote the growth of beneficial bacteria, especially Lactobacillus and Bifidobacterium (Chauhan et al 2014 ; Dhawan et al 2015 ). Thus, the production of oligosaccharides with DP 3–4 makes A. terreus β-mannanase a good candidate for potential application in the feed industry.…”
Section: Discussionmentioning
confidence: 99%
“…β-mannanase is extensively used in the paper/pulp, food, and feed industries, particularly in poultry feeds and prebiotic food supplements to decrease the immunogenic effect of mannan polymers, clarify fruit juices, and extract of oil from copra and detergent (Kaira et al, 2016;Singh et al, 2019). In these industries, thermostable enzymes are preferentially used (Dhawan et al, 2016;Li and Nie, 2016) due to their robustness and enhanced rate of hydrolysis (Katsimpouras et al, 2016;Niu et al, 2017). Moreover, thermozymes offer unique features such as high pH, solvent concentrations (Liu et al, 2019), and resistance to chemical denaturation (Akram et al, 2018), and they could reduce contamination from unwanted microbes (Ebaid et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mannose-free manno-oligosaccharides (MOS) are desirable as prebiotics in nutraceutical industries. Recently, Chauhan et al (2014) and Dhawan et al (2015) have demonstrated the role of MOS as prebiotic in supporting growth of probiotics ( Lactobacillus and Bifidobacterium ) and inhibiting the growth of pathogen ( Salmonella enterica ). The focus of this study is the optimised production of β-mannanase on a solid substrate (PKC), a by-product of palm oil industry, and enzymatic hydrolysis of mannan (locust bean gum and konjac gum) for the generation of MOS.…”
Section: Introductionmentioning
confidence: 99%